Redifining Duty towards an Interdisciplinary Appraisal of Medical Negligence Jurisprudence in the Philippines - Yarcia, Lee Edson P. (Diliman, Quezon City, Philippines: University of the Philippines College of Law)
This note examines recent and leading cases on medical negligence, and analyzes the factors that courts use in determining whether a physician is liable under the law on torts and quasi-delicts. Through an interdisciplinary approach, this Note assesses the functionality of the factors used by courts vis-a-vis the standard of care used by the medical community. Current Philippine literature on medical negligence, reviewing bills on medical malpractice, and exploring the utility of self-regulation in medical malpractice cases. This note focuses on directly appraising the definition of "duty" as currently understood by the courts and proposes the use of an evidence-based medicine framework to reduce variability in practice with an end goal of promoting patient rights and welfare.
Keywords: Medical jurisprudence - Valuation